INDONESIAN CULINARY: NEGOTIATING THE VISUAL AND GUSTATORY PERCEPTION - Sondakh, Sonya Indriati (International Review of Humanities Studies, 2020)
As it concerns the sense of sight, visual culture puts its focus on everything of visual nature. Specific for food, visual culture has played an important role in the development of culinary culture. Corresponding to the rising of visual turn, visual perception has earned its specific role in culinary scene. Regarding this research, it is of great importance to recognise that food has both the visual and gustatory side. Visual relates to the aesthetic side, which is about its visual appearance and gustatory side is about the taste. In food industry led by the Western world with its famous chefs, visual perception is key. When food is served in high-end premises or special places for tourism purpose, visual perception is significant. For Indonesia, one of the tourist attractions is the regional food. Indonesian regional foods certainly have its own unique appearance, but are they acceptable for international culinary standard? Do Indonesian regional foods need to change their visual appearances in accordance with the requirement of the international standard? Using food images taken from the Internet, this article delves into the opposition and negotiation of visual and gustatory perception.